Effects of Cu-deficiency and Ti-excess on Microstructure and Giant Dielectric Properties of CaCu3Ti4O12 Ceramics - Wongtongdee, Piyanud; Thongbai, Prasit (KKU Science Journal, 2023)
CaCu3-xTi4+xO12 ceramics with x = 0 (CCTO) and 0.09 (CCTO-C/T) were synthesized using the solid-state reaction method. The objective was to explore the influence of Cu-deficiency and Ti-excess on the microstructure and dielectric properties of CCTO ceramics. The presence of the primary CCTO phase was confirmed, regardless of deviations in the Cu and Ti molar ratios. The CCTO-C/T ceramic exhibited a secondary phase of TiO2 and segregation of CuO along the grain boundaries. Adjustment of the Cu and Ti ratios hindered grain growth in the CCTO-C/T ceramic. Some CuO segregation along grain boundaries and deficiencies in Ti and Ca were observed in the CCTO-C/T ceramic. Notably, both CCTO and CCTO-C/T ceramics demonstrated a remarkable giant dielectric response of 104. The CCTO-C/T ceramic exhibited a lower loss tangent compared to the CCTO ceramic. Impedance spectroscopy confirmed electrical heterogeneity, with distinct electrical responses attributed to semiconducting grains and insulating grain boundaries. The grain boundary resistance of the CCTO-C/T ceramic was higher than that of the CCTO ceramic, attributed to the presence of segregated CuO and excessive TiO2 phases. Consequently, the concentration of free electrons within the semiconducting grains of the CCTO-C/T ceramic decreased, resulting in a decrease in the giant dielectric response. This study provides valuable insights into the factors influencing the microstructure and dielectric properties of CCTO and CCTO-C/T ceramics, enhancing our understanding of these materials and their potential applications in various technological fields.